Developing Research-Oriented Health Professionals: Understanding Students’ Perceptions and Needs for Extracurricular Research Opportunities - Peihao Xu; Shona Pfeiffer; Fiona Boland; Niall T. Stevens (Journal of Medical Education and Curricular Development)
BACKGROUND Undergraduate training in research principles is often mandated by healthcare profession regulators in Ireland to prepare graduates for higher specialist training. Students can be offered the opportunity to participate in extracurricular research activities, in addition to those embedded in the curricula. This cross-sectional study aims to explore student attitudes towards research and to understand their motivations for engaging in research-related activities and any barriers that might prevent them from doing so. METHODS Students participating in the Royal College of Surgeons in Ireland Research Summer School (RSS) 2023 completed a questionnaire at the start of the program to assess research experience as well as attitudes and motivations towards research. RESULTS Of the 120 participants in the summer research school, only 50 participated in the questionnaire. Of these 50, 42 were medical students. Twenty-nine students were undertaking a supervised research project, while 21 were enrolled in a 4-week taught research skills program. Five students had completed a previous undergraduate or postgraduate degree, and 29 had previously participated in research-related activities. The reasons for participating in the RSS program were to gain experience and skills, followed by having an interest in biomedical research. Twenty-nine students said their motivation was to participate in a more exploratory learning process beyond the syllabus. Thirty students felt the main factor preventing them from gaining research experience was the lack of research opportunities available to them. CONCLUSION Undergraduate health professions students recognize the importance of engaging in research-related activities. Gaining research experiences to enhance knowledge and build professional relations is important, but the lack of opportunities is perceived to be a barrier preventing engagement. Given the value undergraduate students place on research experiences, institutions specializing in health professions education should create customized programs to eliminate obstacles and offer undergraduate opportunities that encourage the development of research-focused healthcare professionals.